ARABISTIKA: JENDELA KECIL KAJIAN ISLAM DI RUSIA (Menelisik Sejarah Awal Pertumbuhan Kajian Islam di Rusia Abad IX-XVIII M) - Z, Wan Jamaluddin (Analisis: Jurnal Studi Keislaman, 2011)
Study on the Islamic studies tradition (orientalism) in Russia is quite rare, whereas compared to the Europeans or the West in general, the Russians actually have far reached into contact with Islam through a variety of traditions and cultures that developed the Arab-Muslim and Arab-Jewish.  This encounter  in the next stage turned into the birth of a tradition encouraging the study of Russian orientalism known as arabistika. This article attempts to trace the history of the growth of Islamic studies in Russia by looking at the factors driving its development and  the  official  policies  of  the  country’s  political  elite,  especially of Peters the Great. The author, in this context, tries to analyze the findings of I.Yu Krachkovsky  on spiritual tour performed by Russian intelligentsia to the Arab world, and the sources of Muh}ammad Na>z}im ad-Daira>wi revealing  the information  and documentation  of ancient Russian that are immortalized  by the some geographers,  historians, prominent Muslim adventurers such as at}-T}abari, al-Maqdisi, al-Idri>si>, al-Mas‘u>di>,  Ibn Khurdadbih, Ibn H}auqal,  Ibn Fad}la>n, Ibnu Bat{u>t}a and many others. This paper also reveal many of the central role of Peter the Great in the development of arabistika tradition in Russia.